Vitamin D deficiency: a cause of clinical concern - Kalra, Sanjay; Goyal, Ramesh (International Journal of Research in Medical Sciences, 2025)
In India, the prevalence of vitamin D deficiency ranges from 35% to 99% despite the fact that India is a tropical country with plenty of sunshine. The prevalence of vitamin D deficiency is high in patients with comorbid conditions such as type 2 diabetes mellitus (T2DM) (84.2%), hypertension (82.6%), and hypothyroidism (76.9%). The effects of vitamin D deficiency are not just restricted to the musculoskeletal system. The presence of vitamin D receptors on the pancreatic beta cells, adipose tissues and skeletal muscle cells indicates the function of vitamin D in the glucose metabolism. Recent literature shows that altered vitamin D and calcium homeostasis may play a role in the development of T2DM. This review delves into recommendation shared by group of expert endocrinologists on skeletal and extra skeletal implications of vitamin D deficiency and the ways to manage patients of vitamin D deficiency. Experts shared that as per guidelines vitamin D deficiency be defined as a 25(OH)D below 20 ng/ml, insufficiency as a 25(OH)D of 21–29 ng/ml, and sufficiency as a 25(OH)D of ≥30 ng/ml. The experts opined that vitamin D levels should be maintained between 40-60 ng/ml for extra skeletal benefits. Vitamin D supplementation has demonstrated potential benefits on glycemic control. Thus, vitamin D supplementation can be added as an effective adjunctive intervention in diabetic and prediabetic patients. Recent advances in technology have enabled delivery of vitamin D through nanoparticle-based Vitamin D which ensure higher absorption and better serum vitamin 25(OH) levels. Experts shared that nano-particle based vitamin D3 appears to be better in achieving higher levels of serum 25(OH)D than that observed with other oral dosage formulations of vitamin D3.